Opioid Overdose and Serotonin Syndrome due to Gastric Bezoar in a Woman with Autism and Pica Behaviour - Palimaru, Iolanda; Guetta, Michaël; Cravero, Cora; Fron, Clémence; Cohen, David; Giannitelli, Marianna (Case Reports in Psychiatry, 2021)
We are presenting the case of a 38-year-old woman with nonverbal autism and intellectual disability, hospitalized in a neurobehavioural unit because of a pica behaviour for 3 years. During the hospitalization, the patient presented an episode of pain, agitation, restlessness, rhabdomyolysis, coma, tachycardia, hyperthermia, shivering, and diarrhoea. The main hypothesis raised was tramadol overdose because of the immediate antidote response to the injection of naloxone 0,4 mg/mL. Even if we did not exceed the recommended prescription dosage of tramadol, the presence of gastric bezoar slowed the absorption of the drug, and the consequence was an opioid overdose and serotonin syndrome.